CFD study of hull wakes in oblique flow at model and full scales. (July 2021) - Zhang, Yu-Xin; Lai, Ming-Yan; Ni, Yin-Gang; Feng, Liang
Highlights: Hull wakes of a bulk carrier in oblique flow are numerically investigated. Scale effect on hull wakes in oblique flow is discussed. The variation in wake velocities on the nominal propeller disk with drift angle is shown and analyzed. Abstract: The characteristic of hull wake for a ship operating in oblique flow significantly affects the ship performance at off-design conditions. This paper presents a numerical study on the hull wakes under oblique flow conditions and analyzes the scale effect. RANS method combined with SST k-ω turbulence model is adopted and an international benchmark ship, Japan Bulk Carrier (JBC), is computed. Drift angles ranging from 0° to 20° with an interval of 5° are considered. Results show that the oblique flow considerably changes the hull wake field. Unlike a left-right symmetric pattern at zero drift angle, the nominal wake in oblique flow conditions shows a strong asymmetry since the flow at the windward side is close to the incoming flow whereas the flow at the leeward side is featured by the vortices detached from the hull. It is also revealed that the mean wake fraction decreases as the drift angle increases. Both model and full scales are simulated and the comparison between them shows significant differences in the wake pattern on the leeward side and the magnitude of the mean wake fraction. Compared with the model scale, the full scale has a stronger aft-body vortex and a smaller mean wake fraction.